2012
DOI: 10.1080/13691058.2011.621450
|View full text |Cite
|
Sign up to set email alerts
|

Modes of (in)tolerance: South African Muslims and same-sex relationships

Abstract: In this study we interviewed members of a small, predominantly Muslim community in Johannesburg, South Africa, in order to ascertain attitudes towards people who engage in same-sex practices. We were interested in ascertaining whether community perceptions of homosexuality match the common (Western) assumption that Islam is profoundly homophobic. Our research, while preliminary, shows that although most people condemn same-sex practices on the grounds of religious principle, they also in practice did not act u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Several participants reported their belief that being gay was permissible provided that one did not ‘flaunt’ gay identity. This narrative is consistent with the observation that homosexuality may be tolerated in Muslim cultures provided that it remains silent, invisible and perpetually subordinate to the dominant heteronormative narrative (Bonthuys & Erlank, ; Murray & Roscoe, ). The perceived tenuity of one's affiliation to the religious group may motivate such adamant defence of the religious in‐group at all costs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Several participants reported their belief that being gay was permissible provided that one did not ‘flaunt’ gay identity. This narrative is consistent with the observation that homosexuality may be tolerated in Muslim cultures provided that it remains silent, invisible and perpetually subordinate to the dominant heteronormative narrative (Bonthuys & Erlank, ; Murray & Roscoe, ). The perceived tenuity of one's affiliation to the religious group may motivate such adamant defence of the religious in‐group at all costs.…”
Section: Discussionsupporting
confidence: 87%
“…Dominant Islamic narratives tend to be in strict opposition to homosexuality (Bonthuys & Erlank, ; Duran, ; Halstead & Lewicka, ; also Yip, ), although there is an emerging ‘reverse discourse’ with some scholars arguing that there is indeed scope for the theological accommodation of homosexuality (e.g. Jamal, ; Kugle, ).…”
Section: British Muslim Gay Men: Identity Threat and Copingmentioning
confidence: 99%
“…The Lesotho penal code is silent about female same-sex practices. However, as in other places in southern Africa, lesbian-identified women are subject to social prejudice and discrimination (Bonthuys and Erlank 2012;Lorway 2006;Ntabe 2010). Despite this stigma, anthropologists have documented a historic and widespread rural practice of ritual recognition of erotic friendships between women as recently as the 1950s (Gay 1986;Kendall 1998).…”
Section: Sexual Practices Identities and Health Among Women Who Havementioning
confidence: 98%
“…Anti-gay attitudes (also referred to as homophobia or sexual prejudice; see Herek & McLemore, 2013) have been evidenced by empirical reports of pervasively negative attitudes among self-identified Islamic individuals (Duyan & Duyan, 2005;Gelbal & Duyan, 2006;Güney, Kargı, & Çorbacı-Oruç, 2004;Rouhani, 2007); however, little work has addressed the factors driving this negativity. Some research suggests that such attitudes are a result of religious scriptural teachings (e.g., Bonthuys & Erlank, 2012;Duran, 1993), while other research has suggested that these attitudes are beyond what is necessitated by the teachings of the Qur'an (e.g., Dossani, 1997;Hooghe, Claes, Harell, Quintelier, & Dejaeghere, 2010). Relative to Christianity, little is known about the relationship between Islam and attitudes towards homosexuality.…”
mentioning
confidence: 99%